MCM6 rs4988235 Allele G, AGT rs699 Allele C, ACE rs4343 Allele A, FADS1 rs174547 Allele C, DCHR7 rs12785878 Allele G, and GC rs7041 Allele T: Candidate Genes for Preeclampsia Prevention - Deviana Soraya Riu; Isharyah Sunarno; Efendi Lukas (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Preeclampsia is the primary cause of maternal and neonatal morbidity and mortality; however, currently there is no definitive method exists to prevent preeclampsia. Recent findings indicate a possible genetic influence on preeclampsia. Therefore, this study was conducted to assess nutrigenomic patterns in preeclampsia as a potential mechanism for identifying appropriate preventive strategies through a nutrigenomic approach.METHODS: This descriptive study focused on 15 primiparous pregnant women diagnosed with preeclampsia. The nutrigenomic test was performed using DNA microarray method to examine variant genes associated with food response and nutrient metabolites. The genetic tendencies were categorized as